In-situ pyrolytic processed zinc stannate incorporated graphitic carbon nitride nanocomposite for selective and sensitive electrochemical determination of nitrobenzene. (28th July 2020) - Vinoth, S.; Mary Rajaitha, P.; Pandikumar, A.
Abstract: In this study describes the in-situ pyrolytic synthesis of zinc stannate-graphitic carbon nitride (ZSO-gCN) nanocomposite material and its potential application in electrochemical sensing of nitrobenzene. The ZSO-gCN nanocomposite was characterized by X-ray diffraction, fourier transform infra-red, X-ray photoelectron spectroscopy, high resolution transmission electron microscopy and elemental mapping to determine the crystalline, morphology, and functionalities of the resultant nanocomposite material. The ZSO-gCN was used to modify the glassy carbon electrode (GCE) surface, and investigated for electrochemical determination of nitrobenzene. The ZSO-gCN modified GCE showed good electrocatalytic activity towards nitrobenzene than other modified electrodes. The ZSO-gCN/GCE having the electron transfer rate constant (ks  = 0.746 s −1 ) and charge transfer coefficient (α = 1.171) towards electroanalysis of nitrobenzene. Linear sweep voltammetric (LSV) technique exhibits cathodic peak current increases in linearly with increasing nitrobenzene content in the range of 30–100 μM. The lowest detection limit (LoD) and sensitivity were found to be 2.2 μM (S/N = 3) and 0.05857 μA μM −1  cm −2, respectively. The inorganic species and organic substances such as Ca 2+, K + and 4-nitrophenol, 1-chloro, 2, 4-dinitrobenzene, 1-bromo, 2-nitrobenzene, 1-iodo, 2-nitrobenzene were showed negligible interference effect with nitrobenzene detection and good sensitivity for monitoring nitrobenzene content in real samples were acquired. This recently produced ZSO-gCN nanocomposite would be a prospective material for electrochemical based sensor applications. Highlights: ZnSnO3 -gC3 N4 nanocomposite material was prepared by in-situ pyrolytic method and used in electrochemical sensing of nitrobenzene for the first time. The lowest detection limit and sensitivity were found to be 2.2 μM (S/N = 3) and 0.05857 μA μM −1  cm −2, respectively. ZnSnO3 -gC3 N4 /GCE has high reproducibility and stability with 2.5 and 5 % relative standard deviation towards nitobenzene. Nitrobenzene detection in real water samples results are satisfactorily using fabricated ZnSnO3 -gC3 N4 /GCE.